Pengaruh Ekstrak Metanol Biji Pepaya Tua dan Ekstrak Metanol Biji Pepaya Muda (Carica papaya L.) terhadap Kualitas dan Kuantitas Spermatozoa Tikus Putih Jantan (Rattus norvegicus) (Effect of Methanolic Extract of Ripe and Raw Papaya Seeds (Carica papaya - Dwi Novita Wijayanti; Siti Muslichah; Endah Puspitasari (Pustaka Kesehatan, 2016)
This research was aimed to determine the effect of antifertility among the methanol extract of ripe and raw papaya seeds in decreasing the quality and quantity of spermatozoa. Animal test rats were divided into 3 groups: negative control (CMC-Na 1%) and the treatment groups given methanol extract of ripe and raw papaya seeds extract. The extracts were given orally for 20 days. On the 21st day, mice were dissected to obtain sperm from the cauda epididymis, then were observed for the quality (motility, viability, morphology) and the quantity of spermatozoa. One-Way ANOVA followed by Post Hoc Test LSD analysis showed that was better for its activity then that of the ripe papaya seed extract. Keywords: ripe papaya seed, raw papaya seed, quality, quantity, spermatozoa